MUSA IBN MAIMUN AL-QURTHUBI AL-YAHUDI (1130-1204 M): INTELEKTUAL SASTRA YAHUDI-ARAB - Ma'mun, Titin Nurhayati; Syaban, Ginanjar; Hazmirullah, Hazmirullah (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2018)
This article discusses a fully-named scientist Abu 'Imran Musa ibn Maimun ibn Abdullah al-Yahudi al-Isra>i>li> al-Qurthubi al-Andalusi> (known as Mí»sí¢ ibn Maimí»n or Moses Maimonides). During his lifetime, he runs various professions, such as rabbis, scientists, and doctors, as indeed have randomness in those fields. However, in this article, the author only focused on the discussion of his figure as a scientist and the works he created. The results of the study showed that Ibn Maimí»n's works contain a thick Arab-Islamic influence. One proof is the use of Arabic language, not Hebrew, in most of his work. That's what makes him categorized as Muslim clerics. His works were incorporated into the Arab-Jewish literary treasures. The results also showed the occurrence of a Jewish-Islamic peace dialogue, high tolerance, and influencing conditions in the field of scholarship. That is what makes it possible to inherit intellectual extraordinarily rich works.